Unpacking the paradox of neighboring ties: the moderating effect of criminal context on victimization - Cwick, Jaclyn M. (Journal of crime and justice, 2018)
The consistency of the finding that neighboring ties produce social control has been challenged in recent work, leading to more nuanced theorizing. Negotiated coexistence theory posits that neighboring ties between criminal and non-criminal residents reduce social control by increasing the negotiating power of the criminal element. The present study tests whether criminal context moderates the relationship between neighboring and victimization. The effect of neighboring, criminal context, and their interaction on victimization outcomes is estimated while controlling for neighborhood disadvantage using ordinary least squares regression among an urban African American cohort. In support of negotiated coexistence theory, findings show that involvement in neighboring within a criminal context is associated with higher violent victimization among men in young adulthood, while neighboring within a non-criminal context is associated with lower young men’s violent victimization. Yet, this relationship does not hold for men in midlife. In contrast, neighboring is associated with lower property victimization regardless of criminal context for women, in line with social disorganization theory; yet, this relationship was only evident in midlife with no such relationship emerging in young adulthood.